The rise of new norms in COVID-19 crisis: learning barriers and opportunities / Che Nooryohana Zulkifli and Nur Afiqah Ab. Latif - Zulkifli, Che Nooryohana; Ab. Latif, Nur Afiqah (Universiti Teknologi MARA, Kedah, 2021)
Covid-19 has been around us for over a year and due to massive restrictions, many nations are still struggling to formulate an ideal education system. As a result of the emergency outbreak, the education system is compromised and this has a direct impact on both instructors and students. The latter were found to experience more significant challenges to continue learning in this crisis, and this requires eclectic strategies for the system to properly function again. Since the number of Covid-19 cases surges every day in Malaysia, it is critical that we address the most pressing concerns that students are currently facing when online learning is abruptly employed to substitute face-to-face (FTF) education. Thus, this paper identified specific challenges faced by the students of Universiti Teknologi MARA Cawangan Pulau Pinang, as well as the opportunities that came with the disruptions that were predicted to be used as optimal ways to receive and distribute online learning information successfully. In this study, 70 participants took part, and the data was gathered through a structured interview that was recorded on videos. The findings demonstrated that, despite the challenges, learners are gradually accepting these new standards, provided suitable learning techniques are used in the education system.